Assymmetric Warfare in Syria: a Challenge to the International Humanitarian Law - Mishchuk, M.; Mishchuk, K. (Університет «КРОК», 2017)
The article examines the application of the International Humanitarian Law (IHL) to the modern warfare, in particular, to the asymmetric confl icts. The purpose of the article is to fi nd out what are the main challenges, which are faced by the IHL in the conditions of the modern warfare. The ongoing confl ict in Syria, which started in 2011, is used as a case study. It shows the real challenges to the IHL and undermines its effective application during the armed confl icts. Thus, the IHL should be developed and modifi ed in the scopes of new types of warfare

В статті досліджується застосування Міжнародного Гуманітарного Права (МГП) до сучасної війни, зокрема до випадків асиметричних конфліктів. Метою дослідження є з'ясування того, які основні виклики стоять перед МГП в сучасних умовах війни. Триваючий конфлікт у Сирії, який розпочався у 2011 році, використовується як приклад дослідження. Події у Сирії показують реальні виклики МГП і підривають його ефективне застосування під час збройних конфліктів. Основним висновком є те, що МГП слід розробляти та змінювати в рамках нових типів бойових дій.
Keywords: Asymmetric warfare; International Humanitarian Law; modern warfare; Syrian conflict; United Nations; ISIS; Noninternational Armed Conflict; Асиметрична війна; Міжнародне гуманітарне право; сучасна війна; Сирійський конфлікт; Організація Об'єднаних Націй; ІДІЛ; Збройний Конфлікт Неміжнародного Характеру